Optimizing biomass and superoxide dismutase in Tetraselmis chuii through stress induction and adaptive laboratory evolution - Khayat, Mohd Ezuan; Halim, Murni; Huang, Zhen Ni (2024)
Microalgae are promising natural antioxidant resources because they adapt to oxidative stresses in harsh oceanic conditions. Limited studies have explored the correlation between antioxidant activities and nutrients or exogenous factors that elevate superoxide dismutase (SOD) levels. Tetraselmis chuii, a marine microalga with high SOD bioactivity, was recently listed as a novel food by the EU Commission. This study aimed to, at first, optimize the production medium to enhance biomass and SOD production in T. chuii, followed by stress induction to further boost SOD bioproduction. The Adaptive Laboratory Evolution (ALE) technique was employed to adapt T. chuii under stressed conditions for SOD enrichment. A two-stage cultivation process was designed: the first stage involved statistical optimization of the cultivation medium to increase biomass. In contrast, the second stage applied various stresses at the late exponential growth phase to induce oxidative stress and trigger SOD production as a defense mechanism.